2002
DOI: 10.1113/jphysiol.2002.026641
|View full text |Cite
|
Sign up to set email alerts
|

Hypotonic treatment evokes biphasic ATP release across the basolateral membrane of cultured renal epithelia (A6)

Abstract: In renal A6 epithelia, an acute hypotonic shock evokes a transient increase in the intracellular Ca2+ concentration ([Ca2+]i) through a mechanism that is sensitive to the P2 receptor antagonist suramin, applied to the basolateral border only. This finding has been further characterized by examining ATP release across the basolateral membrane with luciferin‐luciferase (LL) luminescence. Polarized epithelial monolayers, cultured on permeable supports were mounted in an Ussing‐type chamber. We developed a LL puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 32 publications
4
35
0
Order By: Relevance
“…Activation of P2X receptors increased both sodium and water excretion [168]. Hypotonic treatment evokes biphasic ATP release across the basolateral membrane of cultured A6 cells [106,172].…”
Section: Distal Tubulesmentioning
confidence: 99%
“…Activation of P2X receptors increased both sodium and water excretion [168]. Hypotonic treatment evokes biphasic ATP release across the basolateral membrane of cultured A6 cells [106,172].…”
Section: Distal Tubulesmentioning
confidence: 99%
“…Monolayers on the membrane filters were gently superfused with L-15 medium and equilibrated for 60 min in an Endohm 24 chamber, maintaining the apical and basolateral solution volumes at 2 ml. We quantified ATP release by using an ATP bioluminescent assay kit (Sigma) following a modified method previously reported (8). Briefly, a 500-l sample was taken from the basolateral compartment and added in a mixture of 100 l of luciferin͞luciferase assay reagent and 500 l of L-15 medium in a Petri dish.…”
Section: Measurement Of Transepithelial Electrical Conductance (Gt) mentioning
confidence: 99%
“…In recent work, Jans et al (8) have shown that hypotonic treatment of renal epithelia induces a transient increase in intracellular Ca 2ϩ through a mechanism that is sensitive to the purinergic P2 receptor antagonist suramin applied to the basolateral border only. They demonstrated that ATP was released from the cell and then acted via an autocrine͞paracrine system to produce the suramin-sensitive rise of intracellular Ca 2ϩ .…”
mentioning
confidence: 99%
“…However, this system remains noteworthy because it shows a robust response to changes in tonicity at the basolateral membrane. Here, hypo-osmotic solutions (140 mOsmol; Na + , 70 mM) evoke a pronounced biphasic pattern of ATP release [48]. The first phase was transient and occurred with cell swelling and was replaced by a later tonic phase of sustained ATP release.…”
Section: Enac Modulation By P2rs In the Kidneymentioning
confidence: 99%
“…In turn, ATP stimulates suramin-sensitive P2Rs to increase [Ca 2+ ] int and evoke further ATP release. It was proposed that an ATP plateau was reached only when the rate of ATP release was balanced by the rate of ATP consumption by ectoATPases [48].…”
Section: Enac Modulation By P2rs In the Kidneymentioning
confidence: 99%